2016
DOI: 10.5114/pjp.2016.62027
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells influence neoangiogenesis in prostatic cancer independently of ERG status

Abstract: A significant proportion of prostatic adenocarcinomas show recurrent translocation leading to ERG expression. Previously we found that ERG+ cases have higher microvessel density than negative ones. One factor influencing angiogenesis in cancer is mast cells. The aim of the present study was to evaluate the relationship between microvessels, mast cells and ERG status. In summary, we demonstrated an interrelationship between mast cells, microvascular density and ERG status in prostatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In this context, the immunological response seems to be worth investigating, and it has already been proposed to use tumor vaccines in prostate cancer [15]. Proper understanding of immunological processes is crucial, as many components of the tumor microenvironment, including macrophages, different classes of lymphocytes, NK cells, plasma cells, neutrophils, eosinophils and mast cells, participate in the immune response [16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the immunological response seems to be worth investigating, and it has already been proposed to use tumor vaccines in prostate cancer [15]. Proper understanding of immunological processes is crucial, as many components of the tumor microenvironment, including macrophages, different classes of lymphocytes, NK cells, plasma cells, neutrophils, eosinophils and mast cells, participate in the immune response [16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies were published on the subject, it is still unclear whether translocation-associated prostate cancers are different in morphology or behavior [15]. In our opinion, some differences exist in terms of both morphology and stage as well as interaction with the tumor microenvironment [3,16,17,18]. KDM1A, CHD1, and androgen receptor were identified as forming a complex responsible for targeted DNA breaks, which lead to TMPRSS2-ETS translocation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells (MCs) are enriched in the tumor microenvironment and clinical and experimental studies have confirmed that MCs can promote the occurrence and development of tumors ( Milek et al, 2016 ; Yamashita et al, 2017 ). Mast cell mediators and histamine and histamine receptors may influence the growth of HCC cells, and mast cells and histamine play different roles according to the characteristics of tumor cells ( Lampiasi et al, 2007 ).…”
Section: The Role Of Mast Cells In Liver Cancermentioning
confidence: 99%